LEGAL PROTECTION FOR CREDITORS AGAINST DEBTORS IN DEFAULT PEER TO PEER LENDING AGREEMENT - Marbun, Alvon; Anggi Fitria Nainggolan; Alif Al-Azis Nurullah; Gretta Pertiwi Br; Herman Brahmana; Agus Irawan (Awang Long Law Review, 2024)
The purpose of this research is to determine the validity of the Civil Code perspective on peer to peer lending agreements and to determine the factors that hinder creditor returns and the role of the OJK in protecting creditors. This research uses normative juridical methods, namely obtained from library materials and related literature such as books, journals and so on. Peer to peer lending agreements made using an electronic system are basically valid because they fulfill the 4 requirements in Article 1320 of the Civil Code. There are several factors that hinder returns and creditors, namely, individual characteristics, business, credit, internal and external factors. OJK's role in protecting lenders in peer to peer lending agreements, OJK provides sanctions to organizers for losses from fund owners due to errors and negligence in cases where there is a lack of transparency, not acting fairly, not being reliable, not maintaining data confidentiality and security.